Design method and experiment of machinery for combined application of seed, fertilizer and herbicide - Huang, Xin; Wang, Weiwei; Li, Zhaodong; Wang, Qingqing; Zhu, Cunxi; Chen, Liqing (International Journal of Agricultural and Biological Engineering, 2019)
This study aimed to resolve the problems of full wheat straw returning to the field, which might readily cause stalk obstruction, poor sowing quality, and serious weeds at the seedling stage, affecting the growth of maize. Based on the idea of “simultaneous seeding and spraying, closed weeding”, this paper presented a design method for designing a corn seed-fertilizer-herbicide simultaneous operation machine, which focuses on the design of vertical active straw-removing anti-blocking device mechanism, design of nozzle key parameters, nozzle selection, seeding monomer analysis and spatial layout design of seed-fertilizer-herbicide mechanism. In addition, the interrelated formulas were deduced and machine design and field experiment were conducted. The experiment results showed that the average variation coefficient of spray uniformity of machines was 17.70%. The post-experiment weed amount was 8.9%, which was lower than that before sowing, 8.5% lower than that before artificially closed weeding, and 14.3% lower than that in unenclosed weeding area. Moreover, the weeds were less in the working area of the machine, and the growth of corn was better. Compared with manual closed weeding, the average plant height uniformity and average stem diameter uniformity increased by 4.4% and 5.1%, respectively. Compared with unclosed weeding, the average plant height uniformity and average stem diameter uniformity increased by 18.3% and 10.8%, respectively. Overall, the rationality of the design method proposed in this paper was validated, and these can lay a foundation for the research and development of the same type of machine. Keywords: seed-fertilizer-herbicide, combined application, precision seeding machine, spray device, closed weeding DOI: 10.25165/j.ijabe.20191204.4679 Citation: Huang X, Wang W W, Li Z D, Wang Q Q, Zhu C X, Chen L Q. Design method and experiment of machinery for combined application of seed, fertilizer and herbicide. Int J Agric & Biol Eng, 2019; 12(4): 63–71.